200 years of peruvian foreing policy and its projection in changing world - Novak, Fabián; Namihas, Sandra (Pontificia Universidad Católica del Perú. Instituto de Estudios Internacionales (IDEI), 2021)
Peru’s Ministry of Foreign Affairs was born together with the Republic in 1821. Therefore, it will reach 200 years of institutional life in a few months. This commemoration marked the interest of the authors in carrying out research on the various guidelines of Peruvian foreign policy and, in turn, evaluate whether they have been followed successfully in the past two centuries. This research also had to understand the institutional issue in such a way as to verify if the diplomatic service had been strengthened as an institution and adapted to the changes and needs over time. Here are the results.
Keywords: Política exterior peruana; Derechos Humanos; https://purl.org/pe-repo/ocde/ford#5.04.05